Therapeutic targeting of p90 ribosomal S6 kinase - Wright, Eric B.; Lannigan, Deborah A. (Frontiers in Cell and Developmental Biology, 2023)
The Serine/Threonine protein kinase, p90 ribosomal S6 kinase (RSK) is a downstream effector of extracellular signal regulated kinase 1/2 (ERK1/2) and is activated in response to tyrosine kinase receptor or G-protein coupled receptor signaling. RSK contains two distinct kinase domains, an N-terminal kinase (NTKD) and a C-terminal kinase (CTKD). The sole function of the CTKD is to aid in the activation of the NTKD, which is responsible for substrate phosphorylation. RSK regulates various homeostatic processes including those involved in transcription, translation and ribosome biogenesis, proliferation and survival, cytoskeleton, nutrient sensing, excitation and inflammation. RSK also acts as a major negative regulator of ERK1/2 signaling. RSK is associated with numerous cancers and has been primarily studied in the context of transformation and metastasis. The development of specific RSK inhibitors as cancer therapeutics has lagged behind that of other members of the mitogen-activated protein kinase signaling pathway. Importantly, a pan-RSK inhibitor, PMD-026, is currently in phase I/1b clinical trials for metastatic breast cancer. However, there are four members of the RSK family, which have overlapping and distinct functions that can vary in a tissue specific manner. Thus, a problem for transitioning a RSK inhibitor to the clinic may be the necessity to develop isoform specific inhibitors, which will be challenging as the NTKDs are very similar to each other. CTKD inhibitors have limited use as therapeutics as they are not able to inhibit the activity of the NTKD but could be used in the development of proteolysis-targeting chimeras.